Pengaruh Brand Awareness dan Persepsi Label Halal Terhadap Keputusan Pembelian Produk Personal Care Bagi Pria: The Effect of Brand Awareness and Perceptions of Halal Label on Purchasing Decisions of Personal Care Products For Men - Irfan; Indri Puspita Sari; Ryan Moulana; Novi Safriani (School of Business, Bogor Agricultural University (SB-IPB), 2024)
The purpose of this study was to determine the effect of brand awareness and perceptions of halal label on purchasing decisions for personal care products among students at the Syiah Kuala University (USK). The research was conducted in July - October 2022. This research used a quantitative descriptive method, using a purposive sampling technique. The number of samples was 100 student respondents at USK who had used Kahf's personal care products. The instrument used is a questionnaire that has been tested for validity and reliability. The analytical method used is the classical assumption test analysis and multiple linear regression analysis. Data processing was carried out using SPSS software program version 25. The research data was normally distributed, and there were no symptoms of multicollinearity and heteroscedasticity. The results showed that brand awareness and perceptions of halal label have a posive and significant effect on purchasing decisions for personal care products, either partially or both simultaneously. Regarding the brand awareness variable, the existence of the product is realized mainly from advertising, easy to find, and because of its variety. Meanwhile, in the halal label perceptions variable, consumers trust the product because of the halal label, the guarantee of halalness and the guarantee of being free from the use of haram ingredients. The results of the coefficient of determination test show that the decision to purchase personal care products can be explained by brand awareness and perceptions of halal labels by 53.3%, while the remaining 46.7% is explained by other variables not examined in this study. Keywords: brand awareness, consumer perception, halal label, personal care, purchasing decisions